New value chain management for sticky rice farmers to support the Nang Rong pounded unripe rice business in Buriram province - Ketsripongsa, Udompong; Parat, Sanit; Chanpenkun, Lertpoom (Edelweiss Applied Science and Technology, 2024)
The objectives of this research were 1) to analyze the supply chain of value chain management for sticky rice farmers to support the Nang Rong pounded unripe rice business in Buriram Province; and 2) to develop a new value chain management system for sticky rice farmers by utilizing local resources to support the Nang Rong pounded unripe rice business in Buriram Province. The results revealed that when analyzing the new supply chain of paddy production, the research team collaboratively designed a new supply chain process for rice production, encouraging farmers to voluntarily convert their land to grow sticky rice to meet the demand of Nang Rong pounded unripe rice producers. A total of five groups, comprising 33 farmers, voluntarily participated in the conversion to paddy planting, with a total planting area of 193 rai spread across four sub-districts in Khu Mueang District, Buriram Province. Regarding the development of a new value chain management system for sticky rice farmers for a fair benefit-sharing mechanism, a network of cooperation involving both government agencies, the private sector, and the three groups of stakeholders was established. This network transferred and extended the management results to create a new value chain for Nang Rong pounded unripe rice products in other areas. The project evaluation revealed that the capabilities of entrepreneurs in the five areas were enhanced, resulting in an increase in product value per group per month by 13.12%, and increasing the community’s income by 5.61%.